A critical analysis of the interpretation and application of the “income from trade” requirement contained in section 20(1) of the Income Tax Act, 58 of 1962 with regard to the carrying forward of the balance of assessed losses - Louw, C (Adv.) (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2013.